Environmental regulation of floral anthocyanin synthesis in Ipomoea purpurea - YINGQING LU; JIN DU; JINGYU TANG; FANG WANG; JIE ZHANG; JINXIA HUANG; WEIFENG LIANG; LIANGSHENG WANG (Molecular Ecology, 2009)
Responses of metabolites to environmental fluctuations may play large roles in biological adaptation, yet how these responses initiate in the natural environment and the molecular mechanisms remain unclear. Synthesis of floral anthocyanins, as typical examples of secondary metabolites, is known to respond to the physical environment and therefore an ideal system for understanding the process of the environmental regulation. Here, by simultaneous monitoring of six natural environmental variables and anthocyanin content of daily opening flowers throughout a natural flowering season (∼50 days) of Ipomoea purpurea , we have identified significant and positive correlations of temperature (3‐days ago) and ultraviolet (UV) light intensity (5‐days ago) with the floral anthocyanin content. We sequenced all known (seven structural and three regulatory) anthocyanin genes in I . purpurea flowers and examined their transcript quantities in the natural environment across eight floral developmental stages (covering 0–96 h before anthesis). The anthocyanin gene expression patterns corroborated with the inferred effects from the time‐series data, and further showed that the positive UV effect became negative on transcript levels about 36 h before anthesis. With falling natural temperature, content of the principal anthocyanin declined, whereas that of an alternative anthocyanin with fewer glucose and caffeic acid moieties increased. Our data suggest that environmental regulation of the anthocyanin pathway may account for more than half of the flux variation in the floral limb, and is influenced mainly by daily average temperature and UV light intensity that modulate anthocyanin transcript levels (most likely via myb1 ) at floral developmental stages.